Seed Nutrition and Quality, Seed Coat Boron and Lignin Are Influenced by Delayed Harvest in Exotically-Derived Soybean Breeding Lines under High Heat - Bellaloui, Nacer; Smith, James R.; Mengistu, Alemu (Frontiers in Plant Science, 2017)
The timing of harvest is a major factor affecting seed quality in soybean, particularly in Midsouthern USA, when rain during harvest period is not uncommon. The objective of this research was to evaluate the effects of time of harvest on soybean seed quality (seed composition, germination, seed coat boron, and lignin) in high germinability (HG) breeding lines (50% exotic) developed under high heat. The hypothesis was that seeds of HG lines possess physiological and genetic traits for a better seed quality at harvest maturity and delayed harvest. A 2-year field experiment was conducted under irrigated conditions. Results showed that, at harvest maturity, the exotic HG lines had higher seed protein, oleic acid, sugars, seed coat boron, and seed coat lignin, but lower seed oil compared with the non-exotic checks (Control), confirming our hypothesis. At 28 days after harvest maturity (delayed harvest), the content of seed protein, oleic acid, sugars, seed coat boron, and seed coat lignin were higher in some of the HG lines compared with the checks, indicating a possible involvement of these seed constituents, especially seed coat boron and seed coat lignin, in maintaining seed coat integrity and protecting seed coat against physical damage. Highly significant positive correlations were found between germination and seed protein, oleic acid, sugars, and seed coat boron and seed coat lignin. Highly significant negative correlation was found between germination and oil, linoleic acid, seed coat wrinkling, shattering, and hard seed. Yields of some HG lines were competitive with checks. This research demonstrated that time of harvesting is an important factor influencing seed protein and oil production. Also, since high oleic acid is desirable for oxidative stability, shelf-life and biodiesel properties, using HG lines could positively influence these important traits. This result should suggest to breeders of some of the advantages of selecting for high seed coat boron and lignin, and inform growers of the importance of timely harvest for maintaining high seed quality.